A climate-dependent sustainability index for wave energy resources in Northeast Asia. (15th October 2020) - Kamranzad, Bahareh; Takara, Kaoru
Abstract: In this study, five decades of simulated wave climate in Northeast Asia were used to investigate the intra-annual variation and long-term change of wave energy potential. The results show that in general, the nearshore areas of the eastern Pacific side of Japan have the highest annual mean wave power while Japan and Taiwan function as natural barriers to prevent oceanic waves to propagate from the Pacific Ocean towards Korea and eastern China. The wave energy hotspots vary, seasonally mainly from the east of Japan during the spring to Ryukyu Islands and Taiwan during the autumn, with the highest values in nearshore areas reach around 40 kW/m in September. The results indicate that the intra-annual stability of wave energy resources is the lowest in the western coasts of Japan, whereas this area has contained the least change of wave energy during five decades. On the contrary, southern areas of Japan despite having higher monthly stability show the highest reduction of wave power in the long-term. Hence, a novel index was proposed and applied in nearshore areas in order to specify the most suitable areas for wave energy exploitation considering the sustainability of the resources in both short and long-term. Highlights: 55 years of wave modeling was performed in Northeast Asia. Intra-annual variation and long-term change were assessed. A sustainability index was used to locate the suitable areas for energy extraction.